2008
DOI: 10.1074/jbc.m804478200
|View full text |Cite
|
Sign up to set email alerts
|

MyD88 and Trif Target Beclin 1 to Trigger Autophagy in Macrophages

Abstract: The Toll-like receptors (TLR) play an instructive role in innate and adaptive immunity by recognizing specific molecular patterns from pathogens. Autophagy removes intracellular pathogens and participates in antigen presentation. Here, we demonstrate that not only TLR4, but also other TLR family members induce autophagy in macrophages, which is inhibited by MyD88, Trif, or Beclin 1 shRNA expression. MyD88 and Trif co-immunoprecipitate with Beclin 1, a key factor in autophagosome formation. TLR signaling enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
340
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(354 citation statements)
references
References 31 publications
12
340
0
2
Order By: Relevance
“…Previous studies have demonstrated that both IL1A and IL1B induce autophagy in macrophages, which in turn limits their secretion. 15,17,38 This would suggest a bidirectional feedback mechanism for release of these pro-inflammatory cytokines. A role for MIF in promoting or inhibiting the autophagy-dependent regulation of IL1A and IL1B would be a novel and important finding in the context of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that both IL1A and IL1B induce autophagy in macrophages, which in turn limits their secretion. 15,17,38 This would suggest a bidirectional feedback mechanism for release of these pro-inflammatory cytokines. A role for MIF in promoting or inhibiting the autophagy-dependent regulation of IL1A and IL1B would be a novel and important finding in the context of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus defining the mechanism of action of A46 became more challenging as, instead of being a viral mimic of a host TIR domain that could act as a dominant negative, it is likely a Bcl-2-like protein which targets TIR proteins in a manner not involving homotypic TIR-TIR interactions. It is not unprecedented for TIR proteins and Bcl-2-like proteins to interact, since TRIF and MyD88 can associate with both Beclin-1 and Bcl-2, and are thought to regulate autophagy by disrupting the Beclin1-Bcl2 interaction (50). A46 is part of a family of poxviral proteins either demonstrated or predicted to contain a bcl-2 fold, all of which inhibit PRR signaling, but do so by interacting with diverse and structurally dissimilar host proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is also generally activated by signals evoked by stimulation of PAMP sensors such as TLRs and NOD-like receptors, 11,13,15 and PAMP signal-mediated autophagy is specific to intracellular forms. 39 In response to TLR stimulation, the adaptor protein MYD88 dissociates BCL2 from BECN1 by phosphorylating the latter 40 and the class III phosphatidylinositol 3-kinase complex is formed and initiates autophagy. 41 Meanwhile, the invading microbes are tagged by ubiquitin and associate with the receptor protein SQSTM1.…”
Section: Discussionmentioning
confidence: 99%